Entrepreneurial Product Innovation: A Second-Order Factor Analysis - Damrongrit Niammuad; Kulkanya Napompech; Suneeporn Suwanmaneepong (My University, 2013)
Product innovation is as a vital tool for nascent entrepreneurs seeking to achieve a competitive advantage. This study investigates the integrated and complex relationships that exist between innovation and entrepreneurship by using partial least squares structural equation modelling (PLS-SEM). Entrepreneurial product innovation is tested with second-order factors comprised of entrepreneurial personality, technological opportunity and incubator resources. For this purpose, the empirical research used data from 389 incubated start-ups in Thailand. The study found that these three antecedents are significant for product innovation with effects of varying size. The study magnifies the prominent role of business incubators in fostering entrepreneurial capabilities to boost new products/services. Moreover, the findings suggest that the incubation centre resources mediate the influence of entrepreneurial characteristics by expediting and facilitating product innovation.
Keywords: Incubator; Expediting; Product innovation; Innovation Management; Entrepreneurship Studies and Influences